Meningkatkan Kemampuan Membaca Al – Qur'an Melaui Strategi Simulai Pada Mata Pelajaran Al – Qur'an Hadist Di Kelas VII MTSS Al-Hidayah Sidomulyo - Arlina Arlina; Tengku Alfi Syahrin; Suci Lailannaz; Anisa An’nur Hasibuan; Pebi Nurmala (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This article was created based on the results of research that aims to explain how children's ability to read the Qur'an before using a simulation strategy and find out how to improve their reading skills by using a simulation strategy so that it can provide good results for the next generation. With a good learning strategy, it can produce and improve the ability to read the Koran for Mtss Al-Hidayah sidomulyo students. Previously, researchers found difficulty reading the Koran in class VII students of Mtss Al-Hidayah Sidomulyo. Then the researcher taught the students to read the Koran properly and correctly by using the simulation method and as a result many of the students matched the method we used, so that when the researcher gave the test to the students, they have experienced more or less changes for the better. In this study we used a descriptive qualitative method.